Revitalizing Islamic Education in Bela Negara Universities: Between Ideological Challenges and Religious Value Transformation - Margono, Budi Prasetyo; Karim, Abdul Rahim; Fitriani, Ely (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Islamic Religious Education in non-religious bela negara  universities plays a strategic role in shaping students' moral integrity and spirit of nationalism. However, its implementation faces complex ideological challenges, including campus secularization, plurality of beliefs, and students' pragmatic orientation towards spiritual values. This study aims to analyze the challenges, strategies, and models for revitalizing PAI learning in universities with a bela negara character. This study uses a qualitative method with a phenomenological approach through in-depth interviews, participatory observation, and document analysis of PAI lecturers and students at Universitas Pembangunan Nasional “Veteran” Jawa Timur. The results show that PAI learning is still dominated by a normative- instructive paradigm that is irrelevant to the character of millennial students. The main challenge arises from the tension between universal religious values and national ideology, which is taught formalistically through the bela negara curriculum. To overcome this, a model of revitalization of learning based on religious moderation is needed, which integrates national values through a contextual approach, critical discourse, and the use of dialogical digital learning. This model strengthens the internalization of inclusive and rational Islamic values and fosters loyalty to the Republic of Indonesia. This study confirms that the revitalization of PAI learning is not only a methodological innovation but also an ideological transformation that synergizes the spiritual, intellectual, and nationalistic values of students. These findings are an important reference for the development of the PAI curriculum in non- religious universities with a bela negara character